Science Education Needs of the Individuals with Intellectual Disabilities - Cüneyt Çapraz (Educational Academic Research)
Science class is essential since it covers numerous daily life-related subjects; thus, every student should learn science topics effectively. This study aimed to determine the science education needs of students with intellectual disabilities. While identifying these needs, the study considered ‘the teaching approach of some matters in solid-liquid-gaseous states’ as the basis. It also followed the case study research design, one of the qualitative research approaches. The sample was identified by the purposive sampling method. Four students with intellectual disabilities enrolled in a special education class in a secondary school involved the teaching approach of some matters in solid-liquid-gaseous states. Researchers collected the data through interviews with three special education teachers and one science teacher and through in-class and out-of-class observations in a special education school and two secondary schools retaining special education classes. The collected data were analyzed using the content analysis method. As a result, this study identified both educational-teaching needs and needs for the educational-teaching environment of students with intellectual disabilities.